2018
DOI: 10.3899/jrheum.170904
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-dependent Frequency of Fat Metaplasia and Other Structural Changes of the Sacroiliac Joints in Patients without Axial Spondyloarthritis: A Retrospective, Cross-sectional MRI Study

Abstract: Our study shows a very high prevalence of fat metaplasia adjacent to the sacroiliac joint in asymptomatic patients, while erosions are extremely uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 35 publications
(49 reference statements)
0
23
1
2
Order By: Relevance
“…A recent retrospective, cross‐sectional study of pelvic MRI in a large population of subjects without a rheumatic disease diagnosis found that, although fat lesions were common and increased with age (50.6% of subjects age <45 years versus 94.4% of subjects age ≥75 years), erosions were uncommon (0.6% of subjects age <45 years and 2.6% of subjects in the entire study population) and had no age‐dependent increase . In our study, we found fat lesions in all of the participant groups, although to a much lower extent.…”
Section: Discussioncontrasting
confidence: 52%
“…A recent retrospective, cross‐sectional study of pelvic MRI in a large population of subjects without a rheumatic disease diagnosis found that, although fat lesions were common and increased with age (50.6% of subjects age <45 years versus 94.4% of subjects age ≥75 years), erosions were uncommon (0.6% of subjects age <45 years and 2.6% of subjects in the entire study population) and had no age‐dependent increase . In our study, we found fat lesions in all of the participant groups, although to a much lower extent.…”
Section: Discussioncontrasting
confidence: 52%
“…It is now well established that resolution of subchondral BME in the SIJ may be associated with the appearance of bright tissue on a T1W scan indicating the expression of fatty acids although the histopathology of this tissue is unknown 16–18. While the appearance of fat in the bone marrow may also be physiological,19 20 previous reports have shown that the appearance of post-inflammatory fat metaplasia has characteristic features defined by a distinct border, homogeneous increase in T1W signal and proximity to subchondral bone 21. This lesion has previously been shown to be reliably detected and to be highly specific for SpA,21 22 although questionable to what degree it enhances diagnosis because of the concomitant presence of lesions such as BME and erosion.…”
Section: Discussionmentioning
confidence: 92%
“…Although not required in ASAS definitions of SpA on MRI, the presence of concomitant structural lesions may contribute to diagnosing axial SpA (2). Several studies have examined the presence of inflammatory (4–8,10–13) and structural (4,5,7–14) SI joint features on MRI, such as erosion, fat lesions, sclerosis, backfill, and ankylosis, either individually or in various combinations (14,15), in axial SpA and/or in different conditions. In a recent publication (9), we investigated the diagnostic utility of BME and different structural lesions (i.e., fat lesions, erosion, backfill, and ankylosis) in SI joints identified by MRI according to the Spondyloarthritis Research Consortium of Canada (SPARCC) method (16,17) for differentiating patients with axial SpA from control subjects with or without buttock or pelvic pain.…”
Section: Introductionmentioning
confidence: 99%